2012
DOI: 10.1103/physrevlett.109.064101
|View full text |Cite
|
Sign up to set email alerts
|

Self-Organized Synchronization in Decentralized Power Grids

Abstract: Robust synchronization (phase locking) of power plants and consumers centrally underlies the stable operation of electric power grids. Despite current attempts to control large-scale networks, even their uncontrolled collective dynamics is not fully understood. Here we analyze conditions enabling self-organized synchronization in oscillator networks that serve as coarse-scale models for power grids, focusing on decentralizing power sources. Intriguingly, we find that whereas more decentralized grids become mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
477
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 469 publications
(484 citation statements)
references
References 14 publications
7
477
0
Order By: Relevance
“…Notice that, with the exception of the inertial terms M iθi and the possibly non-unit coefficients D i , the power network dynamics (8)-(10) are a perfect electrical analog of the coupled oscillator model (1) with ω i ∈ {−P l,i , P m,i , P d,i }. Thus, it is not surprising that scientists from different disciplines recently advocated coupled oscillator approaches to analyze synchronization in power networks (Tanaka et al, 1997;Subbarao et al, 2001;Hill and Chen, 2006;Filatrella et al, 2008;Buzna et al, 2009;Fioriti et al, 2009;Simpson-Porco et al, 2013;Dörfler and Bullo, 2012b;Rohden et al, 2012;Dörfler et al, 2013;Mangesius et al, 2012;Motter et al, 2013;Ainsworth and Grijalva, 2013). The theoretical tools presented in this article establish how frequency synchronization in power networks depend on the nodal parameters (P l,i , P m,i , P d,i ) as well as the interconnecting electrical network with weights a ij .…”
Section: Electric Power Network With Synchronous Generators and Dc/amentioning
confidence: 87%
“…Notice that, with the exception of the inertial terms M iθi and the possibly non-unit coefficients D i , the power network dynamics (8)-(10) are a perfect electrical analog of the coupled oscillator model (1) with ω i ∈ {−P l,i , P m,i , P d,i }. Thus, it is not surprising that scientists from different disciplines recently advocated coupled oscillator approaches to analyze synchronization in power networks (Tanaka et al, 1997;Subbarao et al, 2001;Hill and Chen, 2006;Filatrella et al, 2008;Buzna et al, 2009;Fioriti et al, 2009;Simpson-Porco et al, 2013;Dörfler and Bullo, 2012b;Rohden et al, 2012;Dörfler et al, 2013;Mangesius et al, 2012;Motter et al, 2013;Ainsworth and Grijalva, 2013). The theoretical tools presented in this article establish how frequency synchronization in power networks depend on the nodal parameters (P l,i , P m,i , P d,i ) as well as the interconnecting electrical network with weights a ij .…”
Section: Electric Power Network With Synchronous Generators and Dc/amentioning
confidence: 87%
“…Recently, Rohden et at. 12 found that the decentralization of power supply can improve the local stability of the synchronous state. Witthaut and Timme 13 reported that, counterintuitively, addition of transmission lines can harm stability.…”
mentioning
confidence: 99%
“…However, even if the synchronous state is stable against small perturbations, a power grid's state space is also populated by numerous stable non-synchronous states to which the grid might be pushed by short circuits, fluctuations in renewable generation or other large perturbations 5,12,17,18 . Indeed, large perturbations occur so often that a whole subbranch of power grid engineering, called transient stability analysis, has been dedicated to them.…”
mentioning
confidence: 99%
“…For instance, developing clear links between the family of networks generating a specific dynamics and the functional forms of coupling functions may provide a comprehensive framework for designing networks for specific function. Also, formulating optimization schemes based on the results of chapter 2 for increasing (i) the robustness of networks to dynamical perturbations, or (ii) the adaptability to structural perturbations may lead to interesting applications in real-world networks, such as in power grids where one wants to preserve a specific stable dynamics [50][51][52][53]. Also, additional ef-forts should be focused on devising ways to reduce the amount of data necessary to reveal network structural connections.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the structural connectivity is determined by the physical links existing among network units [22]. For instance, the structure of networks of spiking neurons is given by the synaptic connections existing among neurons [11,12], or in power grids, the structural connectivity is defined by the physical power lines connecting the elements in the grid [50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%